Gigantic oocytes in the deep sea black coral Dendrobathypathes grandis (Antipatharia) from the Mar del Plata submarine canyon area (southwestern Atlantic) - Lauretta, Daniel Marcelo; Penchaszadeh, Pablo Enrique (Deep Sea Research Part I: Oceanographic Research Papers)
The black coral Dendrobathypathes grandis (Cnidaria: Antipatharia) is studied for the first time in the southwestern Atlantic off Argentina. This is the only antipatharian reported from the Atlantic between 35°S and 54°S. Eleven specimens were collected at depths of 819–2204 m during three expeditions to the Mar del Plata submarine canyon (2012–2013); seven were females. The species is gonochoric, and the polyps in female colonies contain up to nine oocytes per polyp, which can reach 1500 µm in diameter. In contrast, the largest oocyte currently reported for antipatharians is 500 µm, and usual diameters do not exceed 200 µm. These large oocytes have over 20 times more volume than the biggest oocyte reported, but over 800 times more volume when compared with the common oocyte size of the group. Sperm size and morphology is similar to previous data from other species. As in previous studies, neither embryos nor larvae were found in any specimens. This species was previously only reported from waters off South Georgia Island, and so these specimens expand the known distribution north by 1800 km. Fil: Lauretta, Daniel Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Penchaszadeh, Pablo Enrique. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina